Examining the influence of body fat distribution on standing balance and functional performance in overweight female patients with degenerative lumbar disease - Chen, Jung-Hsuan; Chen, Po-Jung; Kantha, Phunsuk; Tsai, Yi-Ching; Lai, Dar-Ming; Hsu, Wei-Li (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: Degenerative lumbar disease (DLD) is a prevalent disorder that predominantly affects the elderly population, especially female. Extensive research has demonstrated that overweight individuals (categorized by body fat distribution) have a higher susceptibility to developing DLD and an increased risk of falling. However, there is limited research available on the standing balance and functional performance of overweight females with DLD. Aims: To determine the impact of body fat distribution on standing balance and functional performance in overweight females with DLD. Methods: This cross-sectional study evaluated thirty females with DLD were categorized into three types of body fat distribution based on body mass index (BMI) and waist-hip ratio, specifically as android-type, gynoid-type, and normal weight groups. In addition, a control group of ten age-matched females with normal weight was recruited. The Visual Analogue Scale, Roland Morris Disability Questionnaire, Cobb angle (Determined using x-ray), and body composition (Determined using the InBody S10), were conducted only on the DLD groups. All participants were assessed standing balance in the anteroposterior and mediolateral directions. The functional assessments included timed-up-and-go and 5-times-sit-to-stand tests. Results: There were 10 people in each group. Android-type (Age = 65.00 ± 6.34 years; BMI = 26.87 ± 2.05 kg/m2), Gynoid-type (Age = 65.60 ± 4.99 years; BMI = 26.60 ± 1.75 kg/m2), Normal weight (Age = 65.70 ± 5.92 years; BMI = 22.35 ± 1.26 kg/m2), and Control (Age = 65.00 ± 5.23 years; BMI = 22.60 ± 1.12 kg/m2). The android-type group had higher body fat, visceral fat, and lower muscle mass (p<0.05), along with an increased Cobb angle (p<0.05). They showed greater ellipse area, total excursion, and mean distance in the anteroposterior direction (p<0.05). During the functional performance assessments, the android-type group had longer durations in both the 5-times-sit-to-stand and timed-up-and-go tasks (p<0.05). Conclusions: Our study found that android-type overweight individuals showed postural instability, reduced functional performance, and insufficient lower limb muscle strength and mass. These findings might help physical therapists in planning interventions, as they imply that patients with DLD may require specific types of standing balance training and lower extremities muscle-strengthening based on their body fat distribution.